Respuesta :

Answer: [tex]2y^2-4y+5[/tex]

Step-by-step explanation:

The complete exercise is: "What algebraic expression must be subtracted from the sum of [tex]y^2 + 5y - 1[/tex] and [tex]3y^2-2y + 4[/tex] to give [tex]2y^2 + 7y-2[/tex] as the result?"

For this exercise it is necessary to remember that a sum is the result of an addition. Then, if you need to find the sum of [tex]y^2 + 5y - 1[/tex] and [tex]3y^2-2y + 4[/tex] , you need to add them by combining the like terms.

You also need to remember the multiplication of signs:

[tex](+)(+)=+\\(-)(-)=+\\(-)(+)=-\\(+)(-)=-[/tex]

So, you get that the sum of those expression is the following:

[tex](y^2 + 5y - 1)+(3y^2-2y + 4)=y^2 + 5y - 1+3y^2-2y + 4=4y^2+3y+3[/tex]

Since you must find the algebraic expression asked in the exercise, you need to subtract the expression [tex]2y^2 + 7y-2[/tex]  from that sum calculated above.

Therefore, you get:

[tex](4y^2+3y+3)-(2y^2 + 7y-2)=4y^2+3y+3-2y^2- 7y+2=2y^2-4y+5[/tex]

Then, the algebraic expression asked is:

[tex]2y^2-4y+5[/tex]

ACCESS MORE